Propagation of Casuarina junghuniana by Planting Shoots and Root Suckers - Husain, A. M. Mahmood; Ponnuswamy, P. K. (Indian Forester, 1980)
Casuarina junghuniana does Dot produce seeds as the original stock is only male. Therefore it is indispensable to propagate only by vegetative means. This paper describes rooting of sprigs and root suckers Vegetatively.